Hallazgos radiológicos y tomográficos de aplasia pulmonar en un gato (2023)
4-month-old Bengali feline, neutered male, referred for productive cough and respiratory distress without response to treatment. The thoracic radiography reported hyperlucency in the right lung field, soft tissue opacification in the caudal aspect of the left hemithorax, with mediastinal deviation and loss of the cardiac silhouette. Bronchoscopy revealed a rudimentary left bronchus with a blind ending, suggesting pulmonary underdevelopment (SP). Computed tomography (CT) confirmed left lung aplasia with compensatory right lung hypertrophy, ventral and dorsal herniation into the left hemithorax. This is the first published case of CT findings in a feline with pulmonary aplasia. Key Words: congenital, embryology, bronchiectasis.